휴대용 수분스트레스 계측기기를 활용한 과수 수분스트레스 계측 및 진단 - 김희태; 이상봉; 김영진; 김민영; 강상현; Hee-Tae Kim; Sang-Bong Lee; Young-Jin Kim; Min-Young Kim; Sang-Hyeon Kang (농업생명과학연구, 2022)
작물 수분스트레스 지수(CWSI; Crop Water Stress Index)를 통해 관개 시기를 판단할 경우, 정확한 잎의 온도 및 대기 환경을 측정하는 것이 중요하다. 그리하여 본 연구에서는 실시간으로 작물의 생체정보(엽온) 및 대기 환경(대기온·습도, 일사량)을 측정하고 자동으로 CWSI 값이 산정되는 휴대용 수분스트레스 계측기기를 개발하였다. 또한 휴대용 수분스트레스 계측기기와 고정식 온도 측정 방법과의 비교 분석을 통해 휴대용 수분스트레스 계측기기의 성능을 평가하고자 하였다. 본 계측기기는 CWSI 산정을 위한 생체신호 및 기상 데이터를 측정하는 센싱부, 측정된 데이터를 저장하고 CWSI를 산정하는 데이터 수집부, 장치의 기능을 조작하고 측정값을 표시하는 시스템 제어부로 구성하였다. T-test를 실시하여 두 계측 방법에서 측정된 엽온, 일사량, CWSI 평균값의 유의 관계를 분석한 결과, 유의확률은 0.089, 0.318 그리고 0.028로 각각 나타났다. 엽온과 일사량은 유의수준 0.05보다 크므로 유의미한 차이가 나타나지 않았지만 CWSI는 유의확률이 유의수준보다 작으므로 두 측정 방법에 따라 유의미한 차이가 나타났다. When determining irrigation timing through CWSI (Crop water stress index), accurate measurements of leaf temperature and atmosphere conditions are important. In this study, we developed a portable water stress measuring device that measures biometric information (leaf temperature) and atmospheric environment (air temperature & relative humidity and solar radiation) in real time and automatically calculates CWSI. Additionally, the performance of portable water stress device was evaluated by comparing them with fixed measurement methods. The portable water stress measuring devices consists of a sensing unit that measures biological signals and meteorological data, a data collection unit that stores measurement data and calculates CWSI, and a system control unit that manipulates the functions of the device and displays calculated values. An analysis of the significance relationship between the two measurement methods using the T-test showed that the significance probabilities of leaf temperature, solar radiation and CWSI were 0.089, 0.318 and 0.028 respectively. Since the significance probability of leaf temperature and solar radiation were greater than the significance level of 0.05, there was no significant difference. However, CWSI results were less than the significance level, it is judged that the values derived from the two measurement methods are different.